Spontaneous incorporation of gold in palladium-based ternary nanoparticles makes durable electrocatalysts for oxygen reduction reaction - Deli Wang (Nature Portfolio, 2016)
Replacement of platinum is important for lowering the cost of fuel-cell electrocatalysts, but less precious alternatives such as palladium are hindered by lower durability. Here, the authors show that incorporation of trace amounts of gold improves the durability of palladium based oxygen reduction catalysts.